(untitled) (Archaeologia Adriatica, 2026)
In recent years, research on the hillfort settlements of the island of Korčula has intensified, primarily through archaeological excavations at the Kopila hillfort near Blato and the Stine hillfort near Žrnovo. In addition, several hillfort sites have been subject to multiple surveys, one of which is the Smokvica hillfort, positioned above the main transversal route connecting the western and central parts of the island. These three sites have yielded distinctive pottery artefacts that, by their morphological features, correspond to amphorae; however, their dimensions and technological characteristics place them in the category of storage vessels of the pithos type. This paper discusses models that might have inspired their form and offers an interpretation of their provenance as well as their chronological and functional characteristics within the context of the known circumstances of life in the Late Iron Age communities on the island of Korčula.